2019
DOI: 10.1002/ese3.452
|View full text |Cite
|
Sign up to set email alerts
|

Response characteristics of the resistivity and water content during the imbibition process in remolded coal without gas

Abstract: The water content distribution in a coal body is closely related to the gas distribution. It is difficult to directly determine the water content distribution in the process water imbibition. To retrieve the water content by the resistivity value and establish a relationship between the resistivity and water content, the response characteristics of the resistivity and water content of remolded coal formed under different loads are studied by a self‐designed resistivity experimental system. The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The probable source of the saturated zone in the shale matrix of resistivity less than 200 Ωm around a depth of 24 m is a pond near the second ERT. When coal comes in contact with water, its resistivity decreases [55]. The electrical section of profile 2 shows a lower resistivity of the coal, probably because of the saturated coal.…”
Section: Geophysical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The probable source of the saturated zone in the shale matrix of resistivity less than 200 Ωm around a depth of 24 m is a pond near the second ERT. When coal comes in contact with water, its resistivity decreases [55]. The electrical section of profile 2 shows a lower resistivity of the coal, probably because of the saturated coal.…”
Section: Geophysical Studymentioning
confidence: 99%
“…This may be due to more loose sediments between 140 and 280 m of shale. The reduction of the salinity of irrigation water with depth may cause a gradual change in resistivity [55]. The coal seam starts at around 20 m depth and is approximately 60 m × 30 m in size, as interpreted at the center of the profile.…”
Section: Geophysical Studymentioning
confidence: 99%
“…Wang and Jiang found that the imbibition process of static water could enhance coalbed methane recovery. High-energy sites can be easily occupied by water molecules under the action of oxygen-containing functional groups in the coal matrix and hydrogen bonds in water molecules . To summarize, the spontaneous imbibition of external water can lead to four effects, namely, accelerating methane desorption, decreasing the coal seam gas content, eliminating the danger of coal and gas outbursts, and increasing the production of coalbed methane (CBM).…”
Section: Introductionmentioning
confidence: 99%